Patients with Somatic and Comorbid Mental Disorders have Similar Psychological Capacity Impairment Profiles like Patients with Mental Disorders - Muschalla, Beate; Jöbges, Michael (Die Rehabilitation, 2022)
Objectives In patients with somatic illness and additional mental disorder, not only motor or sensory functions may be impaired, but also psychological capacities. These become more and more important for work ability in our modern working world. There are presently no data about the type and distribution of psychological capacity impairments in patients with comorbid somatic and mental disorders. These data are however important for estimation of diagnostic and therapy requirements.Methods 402 orthopedic, cardiological, and neurological patients with additional mental disorders were investigated with a structured clinical assessment for mental disorders (MINI) and psychological capacity impairments (Mini-ICF-APP).Results In all three somatic indications at least half of the comorbid patients had any clinically relevant psychological capacity impairment. Neurological patients (67%) and orthopedic patients (72%) were more often affected than cardiological patients (50.5%). Orthopedic patients are slightly more impaired in self-care; neurological and orthopedic patients are more impaired in mobility; and cardiological patients are less impaired in assertiveness.Conclusion In comparison of all three somatic patient groups with mental disorders the number of psychological capacity impairments is similar. In contrast to patients with mental disorders only (i. e. those without somatic comorbidity), the psychological impairment quality in comorbid patients may be influenced by the somatic illness. The data from this study are important in order to estimate diagnostic and therapeutic needs, such as capacity training or compensation of psychological capacity impairments.
Keywords: Somatic illness; chronic illness; mental disorders; capacities; comorbidities; ICF